The relationship between plants and the Melanau culture in Mukah Sarawak Malaysia - Ismail, Zahora; Hassan, Suziana; Gerten, Adam Haris; Muning, Maznah (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
This ethnobotanical study of Melanau culture in urban residential area analyzes the aspect of the interrelationship between plants and Melanau culture since both provides spiritual connection between people and nature. People rely on plants in many ways. As such, this research has been undertaken to unearth the relationship between plants and the Melanau culture and to identify common plants in an urban environment. Interviews were conducted in Mukah Sarawak to get information and identify people skills with regards to plants. Consequently, identifying plant species helps to preserve the Melanau culture and meanwhile protecting natural heritage and its knowledge.